2008
DOI: 10.3998/ark.5550190.0009.c20
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and elucidation of structure of hydrazones derived from N-(2,4-dimethylphenyl)-3-oxobutanamide

Abstract: Diazonium salts derived from amines 1 (sulfanilic acid, 4-nitroaniline, 4-aminosalicylic acid, sulfanilamide, sulfamethoxazole, sulfathiazole, sulfapyridine, sulfamerazine) were coupled with N-(2,4-dimethylphenyl)-3-oxobutanamide (2) resulting in the formation of hydrazones 3a-h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…The structures of the products were established on the basis of their elemental analyses and spectral data (IR, 1 H NMR, and MS) [see Experimental Part]. In the 1 H NMR spectra of compounds 3a – e , absence of signal assignable to azomethine group (CH–N=N–) [ 37 ] at δ 3.00–4.00 ppm ruled out azo form and supported the hydrazone structure of the products.…”
Section: Resultsmentioning
confidence: 99%
“…The structures of the products were established on the basis of their elemental analyses and spectral data (IR, 1 H NMR, and MS) [see Experimental Part]. In the 1 H NMR spectra of compounds 3a – e , absence of signal assignable to azomethine group (CH–N=N–) [ 37 ] at δ 3.00–4.00 ppm ruled out azo form and supported the hydrazone structure of the products.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies were reported for the biological activities of hydrazide-hydrazone structures [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. The hydrazone group has an advantage of blocking the free amine for metabolic stability.…”
Section: Biological Activitymentioning
confidence: 99%
“…It can be used to prepare azobenzene derivatives with active functional 86 ZANCO Journal of Pure and Applied Sciences 2023 groups as a precursor for further synthesis to give Azo-amide. (Hamzacebi et al, 2008), Azoimine (Ziarani et al, 2018) and Azo-chalcone (Al-Asiri, 2000) Synthetic colors are widely used in many modern sectors, including textiles, leather, paper, and the creation of food and hair coloring. Because of delocalization, the most popular synthetic Azo dyes used for dyeing fabrics and textiles were generally highly colored, i.e.…”
Section: Introductionmentioning
confidence: 99%